Examining the Risks of Multiple Types of Interpersonal Victimization for Transgender and Gender Non-Conforming College Students - Daigle, Leah E. (Journal of interpersonal violence, 2025)
Recent research has shown that transgender and gender non-conforming (TGNC) individuals are at risk of experiencing interpersonal violence, yet there may be differences within this group and across victimization types. The current study examined rates of seven types of interpersonal victimization based on six gender identities (cisgender women, cisgender men, trans women, trans men, nonbinary, and another identity) among a national study of college students. Data from the Spring 2021 American College Health Association’s National College Health Assessment III (ACHA-NCHA III), a national-level study of U.S. college students, were used. We examined the association between gender identity and seven types of interpersonal violence victimization (violent victimization, sexual victimization, intimate partner violence victimization, stalking, bullying, microaggression, and discrimination) that occurred within the past 12 months. Logistic regression analyses were performed to examine if, when controlling for competing factors, gender identity was associated with an increase in the expected odds of victimization for each victimization type. Analyses revealed that TGNC college students reported experiencing a greater amount of all seven types of victimization compared to cisgender college students. These findings corroborate previous research indicating that rates of interpersonal violence are higher among TGNC college students compared to those who identify as cisgender, even after controlling for sexual orientation, related demographic factors, and substance use. Findings from the current study suggest that there are differences within individuals who identify as TGNC in terms of their risk for interpersonal victimization and that rates differ across victimization types. More work is needed to provide tailored prevention programming for TGNC college students.